Analysis of the situation of advertising studies in Spain: Academic offer and reality of the sector - Torres-Romay, Emma; García-Mirón, Silvia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this paper we propose to carry out a review of the current situation of university communication studies from the perspective of its adaptation to the reality of the market. To this end, we monitor the main professional sources that allow us to determine what is being demanded from the advertising communication sector, and then we monitor the current academic offer of the universities in our country, seeking to analyse whether there is a correspondence between supply, demand and, above all, the necessary professional profiles